THE SELECTION PARAMETER FOR THE OPERATION AND MAINTENANCE DAM BASED ON ACTIVITY-BASED COSTING - Juliastuti, Juliastuti; Alisjahbana, Sofia; Wijayanti, Yureana; Mohamad Ma'soem, Dadang; Setyandito, Oki (Journal of Applied Engineering Science, 2024)
Potential risks to people exist if a dam collapses and has a significant impact on the downstream area. Many countries are now facing the problem of having to deal with deteriorated infrastructure due to a lack of maintenance budgeting. This paper presents the dominant parameter in an Operational and Maintenance (OM) dam to build a cost estimation model to maintain the service life of the dam. The method used to identify cost-triggering parameters is based on activity-based costing and dam performance assessments using a combination of the modified Andersen, International Commission of Large Dams (ICOLD), and Dam Commission. The parameter was collected from fourteen independent variables, namely: dam height, irrigation area, sedimentation volume, grass area, wood vegetation area, corrosion area, concrete area, daily worker, corrosion expert, concrete deterioration, hydromechanical, physical performance, operation performance, and safety performance. The results of the model indicate that height, wood vegetation area, concrete maintenance area, hydromechanical deterioration, and safety performance are variables that affect OM costs. The OM costs can be reduced if the safety performance variable increases. This condition implies that if the safety performance component consists of dam monitoring activities, periodic inspections, green belt maintenance, water quality maintenance, and public awareness, the OM costs will decrease by 10%.